Persepsi Anggota Gapoktan “Karya Tani” Pada Pupuk Organik Komsah - Nur Alif, Muhammad Gilang; Suminah, Suminah; Widiyanti, Emi (Hasanuddin University, 2024)
The research is aimed at finding out the perception of members of the Gapoktan